SWOT Analysis and ANP for Organic Tempeh SME Business Development Strategy - Manik Ayu Titisari; Denis Fidita Karya; Surjo Hadi (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: Therefore, in this study, SWOT analysis is used to formulate problems from internal and external factors, from developing alternative strategies, selecting and making strategic decisions that align with company goals. Design/methodology/approach: At the same time, the Analytical Network Process (ANP) is used to weigh each alternative strategy so that the strategy with the highest priority weight can be identified. By using Super Decision software, the best alternative strategy for Soya Agung is to promote promotion and education with a weight of 0.214760. Findings: An industry that can compete in the modern market has the right marketing strategy. As a Small and Medium Enterprise producing tempeh, whose raw material is non-genetic modified local soybeans, Soya Agung still has limitations in marketing its products. Research limitations/implications: The integration of SWOT and ANP is expected to produce strategic plans that can provide various alternative marketing strategies that can help solve company problems. Paper type: Research paper